Baseline Trachoma Surveys in Kaskazini A and Micheweni Districts of Zanzibar: Results of Two Population-Based Prevalence Surveys Conducted with the Global Trachoma Mapping Project. (1st November 2016) - Omar, Fatma J.; Kabona, George; Abdalla, Khalfan M.; Mohamed, Saleh J.; Ali, Said M.; Ame, Shaali M.; Ngwalle, Abel; Mbise, Christina; Rotondo, Lisa; Willis, Rebecca; Flueckiger, Rebecca M.; Massae, Patrick A.; et al.
ABSTRACT: Purpose : Based on health care records and trachoma rapid assessments, trachoma was suspected to be endemic in Kaskazini A and Micheweni districts of Zanzibar. This study aimed to investigate the prevalence of trachomatous inflammation–follicular (TF), and trachomatous trichiasis (TT) in each of those districts. Methods : The survey was undertaken in Kaskazini A and Micheweni districts on Unguja and Pemba Islands, respectively. A multi-stage cluster random sampling design was applied, whereby 25 census enumeration areas (clusters) and 30 households per cluster were included. Consenting eligible participants (children aged 1–9 years and people aged 15 years and older) were examined for trachoma using the World Health Organization simplified grading system. Results : A total of 1673 households were surveyed and 6407 participants (98.0% of those enumerated) were examined for trachoma. Examinees included a total of 2825 children aged 1–9 years and 3582 people aged 15 years and older. TF prevalence in 1–9-year-olds was 2.7% (95% confidence interval, CI, 2.7–4.1%) in Kazkazini A and 11.4% (95% CI 6.6–16.5%) in Micheweni. Among people aged 15 years and older, TT prevalence was 0.01% (95% CI 0.00–0.04%) in Kazkazini A and 0.21% (95% CI 0.08–0.39%) in Micheweni. Conclusion : Trachoma is a public health problem in Micheweni district, where implementation of all four components of the SAFE strategy (surgery, antibiotics, facial cleanliness, and environmental improvement), including mass drug administration with azithromycin, is required. These findings will facilitate planning for trachoma elimination.